Impact of Kishnica and Badovci Flotation Tailing Dams on Levels of Heavy Metals in Water of Graçanica River (Kosovo) - Fatbardh Gashi; Stanislav Frančišković-Bilinski; Halka Bilinski; Agron Shala; Anilë Gashi (Journal of Chemistry)
The main objective of this study was to perform assessment of water quality of Graçanica River (Kosovo), impacted by Kishnica and Badovci flotation tailing dams, using ICP-OES method. The obtained results show that the mean values of all heavy metals in studied river water samples were significantly high, with following maximal concentrations: As (0.033 mgL−1), Cd (0.002 mgL−1), Cr (0.225 mgL−1), Cu (0.015 mgL−1), Hg (0.004 mgL−1), Mn (15.66 mgL−1), Ni (0.255 mgL−1), Pb (0.013 mgL−1), and Zn (0.612 mgL−1), but only two samples from locations influenced by Kishnica and Badovci flotation tailing dams showed statistically anomalous values of Cr3+, Cu2+, Mn2+, Zn2+, and Hg2+. According to assessment based on Croatian standards, locations near both flotation tailing dams are significantly polluted with majority of studied metals, while downstream sampling stations are almost unpolluted or slightly polluted. Mercury is found to be the most significant contaminant. According to WHO recommended values for drinking water, on all locations values were within the limits for Al, Cd, Cu, and Zn, while for As, Cr, Hg, Mn, Ni, and Pb values exceed recommended values on some sampling stations. Further monitoring of water and possibly sediments of Graçanica River is advised, as well as performing of remediation of Kishnica and Badovci mine tailing dams.